Mechanical aptitudes of university women. - Portenier, Lfflian G.; PORTENIER, L G (Journal of Applied Psychology)
The article reports on the administration of the Detroit Mechanical Aptitudes Examination to four hundred twenty-five women students at the University of Wyoming in Laramie, Wyoming during the winter quarter 1942-1943. The Detroit test was chosen since many of the items appeal to girls making the test suitable for both sexes. It was noted that the variation of only one to two percent between the sexes was not believed to be sufficient to warrant complete sets of separate norms. The scores of the university women were about the same as those made by seventh and eight grade boys.